ANALISIS PROGRAM PNPM MANDIRI PEDESAAN TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA KARKITAN BAYAT KLATEN KESEJAHTERAAN MASYARAKAANALISIS PROGRAM PNPM MANDIRI PEDESAAN TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA KARKITAN BAYAT KLATEN - Jima, Jima (Universitas Muhammadiyah Surakarta, 2013)
Povertyis a classic problemthat has been happening in Indonesia.National CommunityÂ Empowerment Program(PNPM)Â is one of thegovernmentprogramsundertakenin an effortÂ tocontrolit.The purposeof this studywas to determine therole ofhuman resource managementin theÂ success ofthe NationalProgramfor Community Empowerment Â (PNPM)Â in the village of Krakitan,Bayat, Klaten. This research is aqualitative descriptive research typeÂ (explanatory), whileÂ thesampletaken by purposive sampling the sampleintentionally predetermined based on theÂ considerationin accordancewith the intentandpurpose of the studycomprised of stakeholders whoÂ knowthe problem sand conditions Krakitan village, Bayat, Klaten.The data was collectedbyÂ observation, Interview Guide or key person, where asthe method usedis AHPÂ (Analytic HierarchyÂ Process). The results ofthe analysis found thatamong manajemnroleof human resourcesisthe mostÂ power ful planning (planning)Â with the eigen vector for 0444 means that44% of the programâssuccess PNPM Rural Krakitan village, Bayat, Klaten played by planning.